2017
DOI: 10.1038/s41598-017-11755-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological activity in calm thermal indoor environments

Abstract: Indoor environmental comfort has previously been quantified based on the subjective assessment of thermal physical parameters, such as temperature, humidity, and airflow velocity. However, the relationship of these parameters to brain activity remains poorly understood. The objective of this study was to determine the effect of airflow on brain activity using electroencephalograms (EEG) of participants in a living environment under different airflow conditions. Before the recording, the room was set to a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In the EEG analysis, we focused on beta and gamma frequency bands since our previous study showed a relationship between these bands and airflow sensations [ 17 ]. The amplitudes were analyzed by each session and frequency band.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the EEG analysis, we focused on beta and gamma frequency bands since our previous study showed a relationship between these bands and airflow sensations [ 17 ]. The amplitudes were analyzed by each session and frequency band.…”
Section: Resultsmentioning
confidence: 99%
“…Some components of EEG signals are known to reflect mental states directly [ 15 , 16 ]. For example, beta and gamma amplitudes were found to be lower under a no-airflow condition than under a direct-airflow condition in a showhouse [ 17 ]. These amplitudes are useful indicators to evaluate comfort feelings with different airflow directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this study suggests that it could be possible to design automatic real-time thermal comfort controllers based on people's HRV. Both research teams from Nkurikiyeyezu et al [10] and Zhu et al [11] have been studied on the Electrocardiogram (ECG) data. The frequency-domain method is adopted to obtain the HRV results and to explore the human thermal comfort under different environments.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relationships between the LF/HF, the thermal sensation and the thermal comfort are also revealed. Hasan et al [12] propose the sensitivity of the PMV thermal comfort model with relative to its environmental factors and personal parameters using the wearable devices. It is found that the expected error range of PMV is high when the other parameters are ignored, such as clothing and metabolic rate.…”
Section: Introductionmentioning
confidence: 99%